1996
DOI: 10.1042/bj3190411
|View full text |Cite
|
Sign up to set email alerts
|

Domain-structure analysis of recombinant rat hormone-sensitive lipase

Abstract: Hormone-sensitive lipase (HSL) plays a key role in lipid metabolism and overall energy homoeostasis, by controlling the release of fatty acids from stored triglycerides in adipose tissue. Lipases and esterases form a protein superfamily with a common structural fold, called the alpha/beta-hydrolase fold, and a catalytic triad of serine, aspartic or glutamic acid and histidine. Previous alignments between HSL and lipase 2 of Moraxella TA144 have been extended to cover a much larger part of the HSL sequence. Fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
166
0
2

Year Published

1997
1997
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 144 publications
(180 citation statements)
references
References 52 publications
12
166
0
2
Order By: Relevance
“…recombinant HSL adi (18)) and the affinity purified rabbit antibody directed toward the GST-HSL-A fusion protein (1:100), described above. A horseradish peroxidase-conjugated donkey anti-rabbit IgG (Amersham Biosciences) was used as secondary antibody (1: 2000) and the blots were developed by enhanced chemiluminescence.…”
Section: Methodsmentioning
confidence: 99%
“…recombinant HSL adi (18)) and the affinity purified rabbit antibody directed toward the GST-HSL-A fusion protein (1:100), described above. A horseradish peroxidase-conjugated donkey anti-rabbit IgG (Amersham Biosciences) was used as secondary antibody (1: 2000) and the blots were developed by enhanced chemiluminescence.…”
Section: Methodsmentioning
confidence: 99%
“…Enzyme activity and acylglyceride assays. The white adipose cell suspension was homogenized and islets were sonicated in buffer (0.25 mol/l sucrose, 1 mmol/l EDTA [pH 7.0], 1 mmol/l dithioerythritol, 20 g/ml leupeptin, 20 g/ml antipain, and 1 g/ml pepstatin A) to allow assay of diglyceride lipase activity, as described elsewhere (20); the diacylglycerol analogue monooleoyl-2-O-mono-oleylglycerol (MOME) was used as substrate (21). ATP and ADP determinations.…”
Section: Methodsmentioning
confidence: 99%
“…The C-terminal portion of HSL displays secondary structural homology with that of acetylcholinesterase and several fungal lipases (5) and bacterial brefeldin A esterase (6), consisting of parallel ␤-sheets flanked by ␣-helical connections, which has allowed these proteins to be classified as ␣/␤-hydrolases (7). Using limited proteolysis, it has been suggested that HSL is composed of two major structural domains (8,9). Based on sequence alignment, structural homology with fungal lipases, and mutational analyses, the C-terminal domain has been shown to contain the catalytic triad and other residues important in hydrolytic activity, as well as a 150-amino acid insert that has been termed the regulatory module because several serines located within this region have been shown to be phosphorylated (1,10).…”
mentioning
confidence: 99%
“…Based on sequence alignment, structural homology with fungal lipases, and mutational analyses, the C-terminal domain has been shown to contain the catalytic triad and other residues important in hydrolytic activity, as well as a 150-amino acid insert that has been termed the regulatory module because several serines located within this region have been shown to be phosphorylated (1,10). The N-terminal domain in rat HSL constitutes the first 323 amino acids, which are encoded by exons 1-4, and displays no sequence or structural similarity with any other known proteins (8,9).…”
mentioning
confidence: 99%